Bedlam on the streets - Knowles, Caroline, 1954- (Routledge, 2000)
This controversial new book traces the terms on which the mad occupy the city's streets, situating this social geography of madness within the broader parameters of systems of globalization and social welfare.
Keywords: Mentally ill -- Care -- Québec (Province) -- Montréal.; Mentally ill -- Québec (Province) -- Montréal -- Social conditions.; Community mental health services -- Québec (Province) -- Montréal.; Mentally ill -- Deinstitutionalization -- Québec (Province) -- Montréal.; Mentally ill -- Services for -- Québec (Province) -- Montréal.; Montréal (Québec) -- Social conditions.; People with mental disabilities.; Community mental health services.; Mental health services -- Québec (Province) -- Montréal.; Persons with Intellectual Disabilities.; Community Mental Health Services; Montréal (Québec); Personnes vivant avec un trouble de santé mentale -- Soins -- Québec (Province) -- Montréal.; Personnes vivant avec un trouble de santé mentale -- Québec (Province) -- Montréal -- Conditions sociales.; Services communautaires de santé mentale -- Québec (Province) -- Montréal.; Personnes vivant avec un trouble de santé mentale -- Désinstitutionnalisation -- Québec (Province) -- Montréal.; Services de santé mentale -- Québec (Province) -- Montréal.; Montréal (Québec) -- Conditions sociales.; Personnes vivant avec un trouble de santé mentale -- Services -- Québec (Province) -- Montréal.; Personnes ayant une déficience intellectuelle.; Services communautaires de santé mentale.; people with mental disabilities.; PSYCHOLOGY -- Mental Health.; PSYCHOLOGY -- Mental Illness.; MEDICAL -- Mental Health.; People with mental disabilities; Mental health services; Community mental health services; Mentally ill -- Care; Mentally ill -- Deinstitutionalization; Mentally ill -- Services for; Mentally ill -- Social conditions; Social conditions; Québec -- Montréal